Microscopic derivation of the hydrodynamic equations for the superfluid fermi-systems - A.Svidzynsky (Condensed Matter Physics, 2005)
Starting from the first principles of statistical mechanics, the two-fluid hydrodynamics of superconductor in ideal approximation is constructed. The system of equations of motion for normal and anomalous correlation functions is used for hydrodynamic description. Transition to equations of hydrodynamics is performed using an expansion of equations of motion for correlation functions in terms of a small parameter.